From perceived social support to prosocial behavior: the serial mediating role of sense of gain and gratitude - Jiali Lin; Tulips Yiwen Wang; Haoxin Liu (BMC Psychology)
Abstract Background Prosocial behavior is conducive to social harmony and personal development. Although some studies have shown that perceived social support can enhance prosocial behavior, the specific mechanisms are not clear. This study establishes a serial mediation model to explore the effects of perceived social support on prosocial behavior and the mediating roles of sense of gain and gratitude. Methods A total of 341 college students aged of 18 to 35(M = 21.52, SD = 2.28, 59.53% female) were surveyed using the perceived social support scale, the sense of gain questionnaire, the gratitude questionnaire, and the prosocial tendency scale. Results The results revealed significant positive correlations among perceived social support, sense of gain, gratitude, and prosocial behavior. Furthermore, gratitude plays a mediating role between perceived social support and prosocial behavior, and the sense of gain and gratitude act as a chain of mediating roles between perceived social support and prosocial behavior. Conclusions The results indicate that enhancing individuals’ perceived social support and increasing their sense of gain and gratitude may be an effective way to promote their prosocial behaviors. However, the cross-sectional design and convenience sampling limit the ability to draw causal and generalizable conclusions.